Smoking and early COPD as independent predictors of body composition, exercise capacity, and health status - Caram, Laura Miranda De Oliveira [UNESP]; Ferrari, Renata [UNESP]; Bertani, Andrï¿½ Luï¿½s [UNESP]; Garcia, Thaï¿½s [UNESP]; Mesquita, Carolina Bonfanti [UNESP]; Knaut, Caroline [UNESP]; Tanni, Suzana Erico [UNESP]; Godoy, Irma [UNESP] (Public Library of Science (PLoS), 2016)
The effects of tobacco smoke, mild/moderate COPD disease and their combined effect on health status (HS), body composition (BC), and exercise capacity (EC) impairment are still unclear. We hypothesized that smoking and early COPD have a joint negative influence on these outcomes. We evaluated 32 smokers (smoking history >10 pack/years), 32 mild/moderate COPD (current smokers or former smokers), and 32 never smokers. All individuals underwent medical and smoking status evaluations, pre and post-bronchodilator spirometry, BC [fat-free mass (FFM) and FFM index (FFMI)], EC [six-minute walk distance (6MWD)] and HS [Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36)]. FFM (p = 0.02) and FFMI (p = 0.008) were lower in COPD than never smokers. 6MWT, as a percentage of reference values for the Brazilian population, was lower in COPD and smokers than never smokers (p = 0.01). Smokers showed worse SF-36 score for functional capacity than never smokers (p<0.001). SF-36 score for physical functioning (p<0.001) and role-emotional (p<0.001) were impaired in COPD patients than smokers. SF-36 scores for physical functioning (p<0.001), role-physical (p = 0.01), bodily pain (p = 0.01), vitality (p = 0.04) and role-emotional (p<0.001) were lower in COPD than never smokers. Multiple linear regression analysis showed that both COPD diagnosis and smoking were inversely associated with FFMI, 6MWD and HS. Smoking and early COPD have a joint negative influence on body composition, exercise capacity and health status.